2012
DOI: 10.1080/09670262.2012.665484
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton sterol contents vary with temperature, phosphorus and silicate supply: a study on three freshwater species

Abstract: The understanding of environmentally induced changes in the biochemical composition of phytoplankton species is of great importance in both physiological studies and ecological food web research. In extensive laboratory experiments we tested the influence of two different temperatures (10 C and 25 C) and a phosphorus supply gradient on the sterol concentrations of the three freshwater phytoplankton species Scenedesmus quadricauda, Cryptomonas ovata and Cyclotella meneghiniana. The diatom C. meneghiniana was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 37 publications
5
36
1
Order By: Relevance
“…However, herbivore sterol limitation might not be restricted to cyanobacteria blooms as eukaryotic algae can also be poor in sterols. In particular, high light intensity and low nutrient availability (for instance in summer) can reduce sterol concentrations in algae below critical levels for herbivorous zooplankton such as Daphnia (Piepho et al, 2010;Piepho et al, 2012). Furthermore, not all phytosterols of eukaryotic algae are suitable precursors for cholesterol, and they vary in their conversion efficiency to cholesterol (Martin-Creuzburg and Von Elert, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, herbivore sterol limitation might not be restricted to cyanobacteria blooms as eukaryotic algae can also be poor in sterols. In particular, high light intensity and low nutrient availability (for instance in summer) can reduce sterol concentrations in algae below critical levels for herbivorous zooplankton such as Daphnia (Piepho et al, 2010;Piepho et al, 2012). Furthermore, not all phytosterols of eukaryotic algae are suitable precursors for cholesterol, and they vary in their conversion efficiency to cholesterol (Martin-Creuzburg and Von Elert, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis confirmed that significant differences were observed between the sampling days but not for the different salinities (Table 5.2). As this effect was independent of changes in salinity, it was likely that the increase in total phytosterol was supported by the dilution of cells on day 11, leading to a lower cell density and a higher light exposure per cell as light was known to play a role in sterol biosynthesis by microalgae (Piepho et al 2012). Notably, the results show that microalgal phytosterol contents higher than 5% DW are achievable in P. lutheri.…”
Section: Induction Of Phytosterol Production In P Lutherimentioning
confidence: 54%
“…Previous studies have shown that availability of nutrients and salility of the cultivation medium may influence phytosterol biosynthesis in microalgae (Francavilla et al, 2010;Piepho et al 2012;Peeler et al, 1989;Zelazny et al, 1995;). When P. lutheri was grown under high nitrate or phosphate concentrations, the sterol contents varied from 5.0 ±0.8 mg/g DW (6P on day 2) to 7.6 ± 0.6 mg/g DW (control on day 10) during the 10 days of cultivation ( Fig.…”
Section: Induction Of Phytosterol Production In P Lutherimentioning
confidence: 99%
See 2 more Smart Citations